2022
DOI: 10.3389/fnmol.2022.937789
|View full text |Cite
|
Sign up to set email alerts
|

Taurine and Astrocytes: A Homeostatic and Neuroprotective Relationship

Abstract: Taurine is considered the most abundant free amino acid in the brain. Even though there are endogenous mechanisms for taurine production in neural cells, an exogenous supply of taurine is required to meet physiological needs. Taurine is required for optimal postnatal brain development; however, its brain concentration decreases with age. Synthesis of taurine in the central nervous system (CNS) occurs predominantly in astrocytes. A metabolic coupling between astrocytes and neurons has been reported, in which as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 165 publications
(219 reference statements)
0
13
0
Order By: Relevance
“…Hence, the reduced taurine response to ethanol might account for the observed decrease of the ethanol‐induced DA response. Even if taurine can be released from both astrocytes and neurons, it is mainly synthesized in astrocytes 41 . The mechanism behind the observed attenuation of ethanol‐induced taurine release is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the reduced taurine response to ethanol might account for the observed decrease of the ethanol‐induced DA response. Even if taurine can be released from both astrocytes and neurons, it is mainly synthesized in astrocytes 41 . The mechanism behind the observed attenuation of ethanol‐induced taurine release is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Even if taurine can be released from both astrocytes and neurons, it is mainly synthesized in astrocytes. 41 The mechanism behind the observed attenuation of ethanol-induced taurine release is not known. It may be due to CIN depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Using in vivo and in vitro mammalian assays demonstrated that the regulation of pyridoxal kinase in thiamine metabolism can affect brain homeostasis ( 34 ). Taurine and hypotaurine have antioxidative, osmoregulatory, and anti-inflammatory functions ( 35 ). Bousquet et al ( 36 ) confirmed that taurine and hypotaurine metabolic pathways have important clinical implications in neurodegenerative diseases by studying key cystamine metabolites, including cysteamine, hypotaurine, taurine, and cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the modification of choline metabolism by exercises could be responsible for protecting against behavioral dysfunction of AD. Taurine is mostly released from astrocytes and has been regarded as an astrocytic biomarker; 70 hence, an increased taurine level in the hypothalamus of AD mice may indicate astrocyte activation and proliferation. 71 Herein a reduced taurine level after exercise especially HIIT suggests that astrocyte dysfunction might be alleviated in the AD brain by HIIT.…”
Section: Discussionmentioning
confidence: 99%